Antioxidant, Antimicrobial, Cytotoxicity, and Larvicidal Activities of Selected Synthetic Bis-Chalcones - Aswathi Moothakoottil Kuttithodi; Divakaran Nikhitha; Jisha Jacob; Arunaksharan Narayanankutty; Manoj Mathews; Opeyemi Joshua Olatunji; Rajakrishnan Rajagopal; Ahmed Alfarhan; Damia Barcelo (Molecules, 2022)
Plants are known to have numerous phytochemicals and other secondary metabolites with numerous pharmacological and biological properties. Among the various compounds, polyphenols, flavonoids, anthocyanins, alkaloids, and terpenoids are the predominant ones that have been explored for their biological potential. Among these, chalcones and bis-chalcones are less explored for their biological potential under in vitro experiments, cell culture models, and animal studies. In the present study, we evaluated six synthetic bis-chalcones that were different in terms of their aromatic cores, functional group substitution, and position of substitutions. The results indicated a strong antioxidant property in terms of DPPH and ABTS radical-scavenging potentials and ferric-reducing properties. In addition, compounds 1, 2, and 4 exhibited strong antibacterial activities against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, and Salmonella enteritidis. The disc diffusion assay values were indicative of the antibacterial properties of these compounds. Overall, the study indicated the antioxidant and antimicrobial properties of the compounds. Our preliminary studies point to the potential of this class of compounds for further in vivo investigation.